Pengaruh Inventory Intensity, Kebijakan Hutang, dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Shilla Anjelina; Adhitya Putri Pratiwi (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of inventory intensity, leverage, and firm size on tax aggressiveness. This study was conducted by analyzing the financial statements of companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. In selecting samples, this study used a purposive sampling technique, namely 145 observation data from 29 selected companies. The data used in this study are secondary data in the form of financial statements from each company that has been used as a research sample. The panel data regression method is used as the research methodology in this study. The analysis of the research results uses the help of Eviews 12 Student Version Lite software. The results of the study indicate that the best model is the Fixed Effect Model (FEM). The results of this study indicate that Inventory Intensity partially has no effect on Tax aggressiveness, Leverage partially has no effect on Tax aggressiveness, Firm Size partially affects on Tax aggressiveness, and simultaneously Inventory Intensity, Leverage, and firm size has a negative affect on Tax aggressiveness.